Pengaruh Komunikasi dan Gaya Kepemimpinan terhadap Kinerja Karyawan (Studi Kasus Gudang Citric Acid Monohydrate Pada PT Golden Sinar Sakti, Tbk) - Mery Anggriani; Asriyal Asriyal (Indonesian Journal of Economics Application (IJEA), 2021)
We write the article to describe the form and analyze the influence of communication and leadership style at PT. Golden Sinar Sakti, Tbk, especially Citric Acid Monohydrate Warehouse Division. The research design used is a quantitative associative method. The data used in this study are primary data, and the sampling technique uses saturated sampling—methods of data analysis using Multiple Linear Regression. Based on the results of data processing, it is found that there is a positive relationship between communication, leadership style, and employee performance at PT. Golden Sinar Sakti, Tbk. The correlation value reached 66.7 percent for the communication variable and 62.6 percent for the leadership style variable. Besides, from the aspect of influence, communication and leadership positively affect employee performance. The magnitude of this influence reached 5.44 percent, while the remaining 45.6 percent was influenced by other factors not examined in this study.